ChemInform Abstract: Ring Modifications in Camphorimines Purely Organic or Promoted by Pt(II). Issue 43 (7th October 2013) - Carvalho, M. Fernanda N. N.; Ferreira, Ana S. D.; Herrmann, Rudolf
Abstract Two new compounds are prepared starting from 3‐oxo‐camphorsulphonylimine (I).